PENGARUH KOMUNIKASI DAN LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI PADA KANTOR PEMERINTAHAN KECAMATAN SIBOLGA SELATAN KOTA - Tiuriska Marbun; H.Kaharuddin; Rosmita Ambarita (Jurnal Mahasiswa: Jurnal Ilmiah Penalaran dan Penelitian Mahasiswa, 2023)
Abstract. Employee performance will be achieved if there is good communication between leaders and subordinates and the work environment supports the implementation of the main tasks and functions. The formulation of the problem in this study is whether communication and the work environment simultaneously influence the performance of employees at the Sibolga Selatan District Government Office, Sibolga City? The purpose of this study was to find out whether communication and the work environment existed simultaneously on the performance of employees at the Sibolga Selatan District Government Office, Sibolga City. The hypothesis in this study is that there is an influence of communication and the work environment on employee performance at the Sibolga Selatan District Government Office, Sibolga City. The type of research used in this research is associative research (relationship) with quantitative data analysis techniques. The total population is 108 people. The sample is used as much as 30% of the population totaling 32 people. Data sources come from primary and secondary data. Data were analyzed using descriptive analysis and quantitative analysis. The results showed that communication and the environment simultaneously had a positive effect on the performance of the Sibolga Selatan District Government Office employees, Sibolga City, where Fcount(23.963) > Ftable (3.30). Partially the communication variable had an effect on employee performance, where the value of t-count2, 664> t table value of 2.036 (2.664> 2.036) or significant (Sig-t) of 0.012 < α (0.05). Partially, work environment variables have a positive and significant effect on employee performance, where the t-count value is 2.600 > ttable value 2.036 (2.823 > 2.036) or significant (Sig-t) of 0.015 < α (0.05). The results of the calculation of the coefficient of determination R Square of 0.623 means 62.3% of employee performance can be influenced by communication and work environment. While the remaining 37.7% can be influenced by other factors not discussed in this study. The multiple linear regression model is 14.857 + 0.303X1 + 0.276X indicating positive performance.